Evaluation of the correlation between Caesium-137 inventory, magnetic susceptibility, and organic matter content to assess soil erosion status in two agricultural fields within El Hachef watershed of northwest Morocco - Meryem Moustakim; Moncef Benmansour; Rabab Bouarfa; Nour Eddine Amenzou; Azouz Benkdad; Brahim Damnati (Heliyon)
Soil erosion by water threatens soil stability in Northwest Morocco. Various techniques have been used to study the phenomenon. This study applies an approach based on measurements of Caesium-137 (137Cs), in situ magnetic susceptibility, and organic matter at two agricultural sites located in El Hachef watershed (Tangier-Tetouan-Al Hoceima region) to evaluate the correlations between these techniques in evaluating the status of soil erosion. Measurements of magnetic susceptibility, 137Cs, and organic matter were taken along two parallel transects in Field 1 and a single transect in Field 2. A stable reference site near the studied fields was selected and sampled to represent the initial 137Cs stock in the area. Soil stability in the two agro-systems is evaluated and compared with the reference site. In the reference site, the mean 137Cs activity is 1707 Bq/m2, magnetic susceptibility is 0.296∗10−3 SI, and organic matter content is 8.15 %. In Field 1, 137Cs activities range from 135 to 1586 Bq/m2, magnetic susceptibility measurements range from 0.009∗10−3 SI to 0.169∗10−3 SI, and organic matter content varies between 4.41 % and 7.74 %. In Field 2, 137Cs activities range from 88 to 1558 Bq/m2, magnetic susceptibility measurements range from 0.021∗10−3 SI to 0.165∗10−3 SI, and organic matter content varies from 3.81 % to 7.22 %. The results show that the areal activities of 137Cs and magnetic susceptibility measurements are highly correlated (around 80 %) and the correlation factors for these parameters with the organic matter are over 70 % and 60 %, respectively. Estimated erosion rates based on Mass Balance Model 2 are 28.4 t/ha/yr in Field 1 and 42.7 t/ha/yr in Field 2. The multidisciplinary approach highlights the complementarity nature of the measured parameters in documenting soil movements.